Increasing of Students’ Motivation in Learning Physics Through the Use of Computer Simulation Media Viewed From Parents’ Employment Background - Yusrizal, Yusrizal; Hanif, Khairul (SCAD Independent, 2017)
This study aims to determine the increasing of high school students’ motivation in learning physics through the use of computer simulation media in terms of parents’ employment background. The method used in this study is quasi-experimental method. This research was conducted in class X SMAN 1 Lhoknga Aceh Besar. The data collection was gathered by giving a pretest and posttest questionnaire of student motivation. Then, the administration of a questionnaire survey was conducted to find out the background of the parents’ employment. The results of the study showed that the use of computer simulations media could increase student motivation. The survey results showed that in the experimental class the student whose father works as a vegetable seller and his mother as a housewife got the highest increase of motivation. Furthermore, students who experienced the lowest increase of motivation both parents were victims of tsunami disaster in 2004. In the control class, students who experienced the highest increase of motivation came from a family whose father works as a fisherman and his mother is a housewife. Whereas, Students who obtained the lowest increase of motivation, his father has temporary jobs and his mother is a housewife.